The sociological measurement of individual adaptive potential in media ecosystem - O. A. Grimov (Цифровая социология)
The article presents the theoretical justification and empirical approbation of the author’s model of the individual adaptive potential in the conditions of the media ecosystem. The basis of the author’s approach is the consideration of the individual as the main subject of media activity practices that actualise the personal resources of Internet users associated with their readiness for effective communication, for production and consumption of media content in modern institutional conditions of the media ecosystem (considering existing risks and limitations). A theoretical model of adaptive potential is proposed, according to which such a potential is a complex multi-level education containing three successive levels: value, dispositional and practical. It is shown that each level consists of a number of sublevels, of including the types of values, dispositions and users’ practices prevailing in the media ecosystem. Based on the development of these operational indicators and a special scale, the author’s methodology for the adaptive potential sociological measurement of the individual in the media ecosystem is presented. According to the results of the author’s sociological research with the usage of cluster analysis (online survey of social networks and messengers’ users, N = 900), four clusters of media users were found, differing in the level of development and structure of adaptive potential. These clusters are characterised as “cautious users”, “theorists”, “unadapted”, “adapted”. The article concludes with promising directions for further scientific research on the topic.